Customer Value Generation in Banking The Zurich Model of Customer-Centricity - Auge-Dickhut, Stefanie; Koye, Bernhard; Liebetrau, Axel (Management for Professionals, 2016)
The banking sector is undergoing a process of fundamental transformation - mainly due to the challenges of digitalization, insistent customers, regulation and a volatile economic environment. This book provides an in-depth understanding of the underlying logic of 21st century's banking environment and helps to develop a roadmap for the successful transformation of contemporary business models. The authors introduce the 'Zurich model for a customer-centric banking architecture' enabling the reader to develop a sustainable business model which copes with the challenges of this information age. They identify customer behavior traps in such an environment; introduce adequate strategic instruments and cornerstones for providing added value through financial services, and provide core factors for conducting a successful transformation process.